CULTURE SHOCK: PENGELOLAAN KECEMASAN DAN KETIDAKPASTIAN DIRI PADA MAHASISWA PERANTAU DI YOGYAKARTA - Seiren Ikhtiara (Universitas Tidar, 2025)
Students who migrate from outside Java Island to Yogyakarta often face cultural adaptation challenges that trigger anxiety and self-uncertainty. Differences in values, norms, and communication styles lead to their perception as